The methodology of using neural networks in the fine arts of contemporary Chinese artists - Andreeva, Mariia Алексеевна (Известия Саратовского университета: Новая серия. Серия Философия. Психология. Педагогика, 2025)
Introduction. Contemporary artists increasingly resort to new ways of creating works of art – there is a constant introduction of neural network programs and new methods, which leads to qualitatively new results and new artistic thinking. In this case, the experience of China is especially interesting, where artificial intelligence developments are being introduced at the legislative level into the creation of works of art. Theoretical analysis. There are several concepts that consider creativity and authorship in the era of artificial intelligence. Researchers agree that we are now in the era of co-authorship with neural networks, as they can bring new elements to the original idea of the artist. Chinese authors actively use ChatGPT, Midjourney and other neural networks to develop and improve their ideas. Conclusion. The methodology of using neural networks enriches the creativity of contemporary artists, but at the same time, it can become a threat to the cognitive abilities of future authors.